Hfq‐dependent mRNA unfolding promotes sRNA‐based inhibition of translation - Hoekzema, Mirthe (EMBO J, 2019)
Small RNAs post‐transcriptionally regulate many processes in bacteria. Base‐pairing of sRNAs near ribosome‐binding sites in mRNAs inhibits translation, often requiring the RNA chaperone Hfq. In the canonical model, Hfq simultaneously binds sRNAs and mRNA targets to accelerate pairing. Here, we show that the Escherichia coli sRNAs OmrA and OmrB inhibit translation of the diguanylate cyclase DgcM (previously: YdaM), a player in biofilm regulation. In OmrA/B repression of dgcM, Hfq is not required as an RNA interaction platform, but rather unfolds an inhibitory RNA structure that impedes OmrA/B binding. This restructuring involves distal face binding of Hfq and is supported by RNA structure mapping. A corresponding mutant protein cannot support inhibition in vitro and in vivo; proximal and rim mutations have negligible effects. Strikingly, OmrA/B‐dependent translational inhibition in vitro is restored, in complete absence of Hfq, by a deoxyoligoribonucleotide that base‐pairs to the biochemically mapped Hfq site in dgcM mRNA. We suggest that Hfq‐dependent RNA structure remodeling can promote sRNA access, which represents a mechanism distinct from an interaction platform model.